Kahon - Mangaran, Mon Karlo L. (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
Most of us lived inside a box during the pandemic, especially the poor and oppressed, trapped within a society led by an apathetic regime. The pandemic exposed our weak healthcare system, contrary to the claims of the government. It was not only the COVID-19 virus that has killed our fellow Filipinos but also a very rotten system that denied us of our basic human needs such as housing, access to health services, and a living wage.